MODEL IMPLEMENTASI KEBIJAKAN VAN METER DAN VAN HORN DALAM TINJAUAN PEMBANGUNAN JALAN LINGKAR SELATAN (RING ROAD) DI KABUPATEN TUBAN - Wennyta Eka Fauziyah; Lukman Arif (Journal Publicuho, 2021)
This study aims to determine how the policy implementation of South Ring Road development in Tuban District that analyzed using the policy implementation model from Van Meter and Van Horn (1775). The type of research used is the type of qualitative research with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that all indicators of the policy implementation model from Van Meter and Van Horn (1975) as a measure of the success of the policy implementation of South Ring Road development in Tuban District are due to minimal financial resources, causing poor road construction. failure to achieve standards, inaccuracies and inconsistencies in communication during the policy implementation process which caused problems, and the presence of people who did not support the development policy of the Ring Road. So it can be concluded that the policy implementation of South Ring Road development in Tuban District has not run optimally